IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENGHADAPI ERA BERCIRIKAN VUCA - syamsul bahri (Yayasan Hurriah, Banda Aceh, 2022)
English: This paper aims to show how the digital world defined by VUCA (Volatility, Uncertainty, Complexity, and Ambiguity), has a significant impact on the implementation of human resource management in educational institutions. The data of this paper were collected through literature study and data analysis of various materials related to human resource management in the VUCA era, such as books, journals, and websites, and then examined descriptively. The findings of this study indicate that in the management of human resources in educational institutions, three strategies should be used to thrive in the VUCA era and turnover cycle: leadership strategy, product differentiation, and low cost strategy. Following up on these results, institutional leaders as the driving force for human resource management must have service breakthroughs that can get out of the VUCA trap so that educational institution services are in line with the demands of the VUCA period. Bahasa: Tulisan ini bertujuan untuk menunjukkan bagaimana dunia digital yang didefinisikan oleh VUCA (Volatility, Uncertainty, Complexity, dan Ambiguity), memiliki dampak yang signifikan terhadap implementasi manajemen sumber daya manusia di lembaga pendidikan. Data makalah ini dikumpulkan melalui studi kepustakaan dan analisis data dari berbagai bahan yang berkaitan dengan manajemen sumber daya manusia di era VUCA, seperti buku, jurnal, dan situs web, dan kemudian diperiksa secara deskriptif. Temuan penelitian ini menunjukkan bahwa dalam pengelolaan sumber daya manusia di lembaga pendidikan, tiga strategi harus digunakan untuk berkembang di era VUCA dan siklus perputaran: strategi kepemimpinan, diferensiasi produk, dan strategi biaya rendah. Menindaklanjuti hasil tersebut, pimpinan lembaga sebagai motor penggerak pengelolaan sumber daya manusia harus memiliki terobosan layanan yang dapat keluar dari jebakan VUCA agar layanan lembaga pendidikan sejalan dengan tuntutan masa VUCA.